Разработка концепции комплексной программы организационно-экономических мероприятий мотивации труда персонала энергетических предприятий - Минкович, А. В.; Костин, Д. Ю. (НТУ "ХПИ", 2014)
В статье рассмотрена концепция построения комплексной программы оргнизационно-экономических мероприятий мотивации труда персонала энергетических предприятий. Определена роль мотивации труда персонала в достижении стратегических целей развития предприятия, предложен механизм разработки комплексной программы организационно-экономических мероприятий мотивации труда персонала энергетических предприятий.

The paper considers the concept of building a comprehensive program economic measures for motivation of staff in energy companies. It determines the role of staff motivation in achievement of strategic objectives of the company's development, offers a mechanism for development of a comprehensive program of organizational and economic measures for motivation of staff in energy companies.
Development of the concept of the comprehensive program of organizational and economic measures for motivation of staff in energy companies
Keywords: механизм; стратегические цели; развитие предприятия; кадровая политика; доходы; инвесторы